2016
DOI: 10.3390/ijerph13090860
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Community and Individual Level Social Capital with Activities of Daily Living and Death by Gender

Abstract: This study determined whether there is an association between social capital and a composite outcome of decline in Activities of Daily Living (ADL) and death by gender. A prospective 3.5 year cohort study was conducted in a rural town in Japan. The study participants were 984 individuals aged 65 years and older with not impaired on ADL at 2010 baseline survey. Social participation and generalized trust were measured as social capital. The individual level responses were dichotomized and aggregated into the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
25
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 40 publications
2
25
1
2
Order By: Relevance
“…Seventeen studies were considered of good quality, 42,47,53,57‐59,61,68,69,74,75,78,84,85,96,98,99 31 were fair quality, 15,37,38,40,41,44‐46,50,51,54,56,60,62‐67,72,76,77,79,81,83,86,88,91‐93,97 and 17 were poor quality 36,38,43,48,49,52,55,70,71,73,80,82,87,89,90,94,95 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seventeen studies were considered of good quality, 42,47,53,57‐59,61,68,69,74,75,78,84,85,96,98,99 31 were fair quality, 15,37,38,40,41,44‐46,50,51,54,56,60,62‐67,72,76,77,79,81,83,86,88,91‐93,97 and 17 were poor quality 36,38,43,48,49,52,55,70,71,73,80,82,87,89,90,94,95 …”
Section: Resultsmentioning
confidence: 99%
“…In other studies, functional decline was assessed by means of access to public long‐term care services 37,41,60,63,64,67,68,71,81,87,88 . One study considered functional decline by means of years with active life 62 whilst in another study, a functional decline measurement was not described 59 (On‐line Appendix [Outcome Definition]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Marital status has also been identified as an important social factor associated with mortality, and married people are more likely to engage in healthy behaviors (and less likely to engage in unhealthy ones) than widowed, divorced, or single people . An association has been identified between lack of social and family support and development of noncommunicable chronic diseases in elderly people, and we previously reported that inadequate social capital is associated with a decline in ADLs and death . Therefore, we focused in the current study on how living circumstances and marital status might influence the association between depressive symptoms and future functional impairment.…”
mentioning
confidence: 99%
“…11 An association has been identified between lack of social and family support and development of noncommunicable chronic diseases in elderly people, 12 and we previously reported that inadequate social capital is associated with a decline in ADLs and death. 13 Therefore, we focused in the current study on how living circumstances and marital status might influence the association between depressive symptoms and future functional impairment. Japan's Cabinet Office has reported that Japan has a large proportion of elderly people living alone, and that they are more likely than elderly people in other countries to rely on family than neighbors when they are sick.…”
mentioning
confidence: 99%